MENGGALI POTENSI ALIRAN AIR SUNGAI SEBAGAI SUMBER TENAGA PEMBANGKIT LISTRIK MIKROHIDRO; STUDI KASUS : SUNGAI KALI MANGGIS DI WILAYAH MAGELANG - Nisworo, Sapto; Setyowati, Endang (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2008)
People are becoming more dependent on electric energy in their daily life. Waterfall is one potential primary source of energy. Kali Manggis river has to potential for a PLTM (Pembangkit Listrik Tenaga Mikrohidro) system used waterfall method. The research was to explore this potential quantitatively.This research used positivistic method with a hypothesis that Kali Manggis river is good potential of energy. Discharge of water and the height of waterfall were measured and the analysis of data will give quantity energy.The findings show that Kali Manggis river was a lot of power for electric energy. The electrical energy force in the Kali Manggis river was 1.503,8222179 kwh.